Antiepileptic drug therapy in autoimmune epilepsy associated with antibodies targeting the leucine‐rich glioma‐inactivated protein 1. Issue 3 (25th June 2018) - Feyissa, Anteneh M.; Lamb, Christopher; Pittock, Sean J.; Gadoth, Avi; McKeon, Andrew; Klein, Christopher J.; Britton, Jeffrey W.
Summary: Objective: To characterize seizure semiology and the utility of antiepileptic drug (AED) therapy in leucine‐rich glioma inactivated‐1 ( LGI1‐Ab) autoimmune epilepsy (AE). Methods: Patients with voltage‐gated potassium channel complex (VGKCc) titers higher than 0.02 nmol/L who were evaluated between May 2008 and June 2016 at the 3 Mayo Clinic sites (Arizona, Florida, or Minnesota) were identified. We then performed a retrospective review of those who were LGI1‐Ab positive and were treated for seizures. Results: A total of 1, 095 patients with VGKCc titers higher than 0.02 nmol/L were identified, in which 77 were LGI1 positive. Of these, 56 patients with seizures were included in the analysis. Mean age at symptom onset was 62.9 years; 66% (n = 37) were male. The most common seizure semiology was focal faciobrachial dystonic seizures with preserved awareness (FBDS) (n = 35, 63%), followed by focal with impaired awareness (FIA) (n = 29, 52%), generalized tonic–clonic (GTCs) (n = 28, 50%), and focal non‐motor seizures with preserved awareness (n = 28, 50%). The majority had more than one seizure type (n = 49, 88%; median = 2.5). Thirty‐eight patients (68%) became seizure free: 29 (76%) with immunotherapy, 3 (5%) with AEDs alone, 2 (3%) with AEDs before any immunotherapy, and 4 (7%) with AEDs after immunotherapy. Levetiracetam (n = 47, 84%) and valproic acid (n = 21, 38%) were the most commonly used AEDs, but neither were associated with seizure freedom. Sodium channel blocking (NCB) AEDs were associated with seizure freedom in 4 patients compared to none treated with non‐NCB AEDs. Regardless of class, AEDs prior to or apart from immunotherapy were associated with seizure freedom in only five patients (9%). In patients with FBDS, seizure freedom was more often associated with immunotherapy than AEDs (20/30 vs. 3/34, p = 0.001). Significance: Although FBDS are the most characteristic seizure type seen in LGI1‐Ab AE, other seizure types including FIA and GTCs also occur. Immunotherapy was the treatment most frequently associated with seizure freedom in LGI1‐Ab AE. In general, AEDs seemed to confer a very low chance for seizure freedom, although AEDs with NCB‐blocking properties were associated with seizure freedom in a limited number. Levetiracetam in particular appears to be ineffective in this patient population.